Why STEM? Why now? Educating for technologies, or technologies for education?. (3rd July 2018) - Tan, Michael
ABSTRACT: The STEM movement is a recent phenomenon receiving worldwide attention as the darling educational project for school systems and research centres. This interest has no doubt been fuelled by economic rationales of the supposed necessity of STEM for continued material wealth, and the claims that the future will require a different sort of expertise than what we currently possess. However, not as a conservative response, but as a critical one, it is important for us to become clearer about what it is that we would want students to learn. In addition, as researchers and practitioners, it is imperative that we distinguish hype from reality, if only because we need to learn from our collective institutional histories and claim some form of ownership over the direction of our work. Interdisciplinary STEM education does provide opportunities for educators to deeply confront such issues as the ethics of invention, and the distinction between the descriptive and normative disciplines. Yet, these gains are likely to be drowned out by the much louder clamour for flashy new things to fill new rooms with rearranged furniture. This commentary is intended as a reminder to the community to do the hard, unglamorous work required to make worthwhile learning happen.